The UK media coverage of China’s handling of the coronavirus outbreak - Zhang, Xiaoling; Shaw, Gareth (SAGE Publications Ltd, 2020)
This article addresses one question: how is the coronavirus outbreak and its management in China reported in the UK media in general, and on the Internet in particular? It does so by examining how the online versions of the BBC, the Guardian and the Daily Mail reported on the coronavirus outbreak in China, but more importantly, on how China handled it, over a 20-week timeframe. The sentiment analysis and thematic analysis show that although the selected media are of different types in the United Kingdom, the themes and topics are not substantially different from each other. This implies that the general media-consuming public in the United Kingdom would regard China’s handling of the virus as largely negative or neutral. However, the ways of discussing and presenting those topics were subject to variation between the publications, which in turn is reflected in the attitudes and perceptions of their readers.